STUDI PERSEPSI MAHASISWA FISIP PADA PESAN POLITIK GERAKAN #2019GANTIPRESIDEN DI TWITTER - Sitti Utami Rezkiawati Kamil, Eka Wulandari, Zulfiah Larisu (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2019)
ABSTRACT  This survey aims to determine the perception of FISIP students of movement political message #2019GantiPresiden in Twitter. The subject in this survey were FISIP students who actively used twitter and knew phenomenon of political message #2019GantiPresiden in Twitter with eight informants the technique of informant used was technique purposive sampling  data collection technique used were observation, interview and documentation. Data analysis technique used in this survey were descriptive qualitative, which was to describe ,analyze, and describe conclusions from the results of research that were related to relevant theories.The resuts of this survey indicate that based on the perception given by FISIP students not derectly accepted political message #2019GantiPresiden in Twitter. Related to the obstinate audience theory by Raymond Bauer. This research showed that after FISIP students got political message #2019GantiPresiden in Twitter, student did not immediately made decisions for accepted or rejected political message #2019GantiPresiden. However, there was a screening and selection process for the political message in other words FISIP student accepted political message #2019GantiPresiden in Twitter if it matches the argument and met its political interested. Most FISIP students knew the phenomenon #2019GantiPresiden trough via social media Twitter and partly through other media. FISIP student response to political message #2019GantiPresiden the majority don't like because this political message many hoax and hate speech. This affects the lack of power of political messages #2019GantiPresiden to FISIP students of Halu Oleo University.                       Keywords: Perception, political message, #2019GantiPresiden, Twitter, FISIP student